2016
DOI: 10.1111/jvim.13814
|View full text |Cite
|
Sign up to set email alerts
|

Breed Distribution and Clinical Characteristics of B Cell Chronic Lymphocytic Leukemia in Dogs

Abstract: BackgroundB‐cell chronic lymphocytic leukemia (B‐CLL) is the most common hematopoietic malignancy in humans in the developed world and the primary risk factor is genetic. Dogs also develop B‐CLL, but there is no systematic description of the disease in dogs. Understanding the epidemiology of B‐CLL in dogs may help practitioners recognize the disease and position the dog as a model for future genetic studies.ObjectivesTo describe B‐CLL presentation in dogs, its clinicopathologic findings, and breed predispositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 30 publications
1
59
2
Order By: Relevance
“…Unlike the human disease, canine B-CLL cells do not express CD5. It is seen primarily in small breed, older dogs (66). Strikingly, despite the prevalence of large breed dogs such as German shepherds and Golden retrievers in the population of cDLBLC, these breeds virtually never develop B-CLL (66).…”
Section: B Cell Cllmentioning
confidence: 99%
“…Unlike the human disease, canine B-CLL cells do not express CD5. It is seen primarily in small breed, older dogs (66). Strikingly, despite the prevalence of large breed dogs such as German shepherds and Golden retrievers in the population of cDLBLC, these breeds virtually never develop B-CLL (66).…”
Section: B Cell Cllmentioning
confidence: 99%
“…A diagnosis of TZL included greater than 60% of the lymphocytes characterized as TZ cells (CD5+ CD45− cells) in lymph node samples or the presence of ≥5000 TZ cells/μL in the peripheral blood of dogs with lymphadenopathy or lymphocytosis, respectively. These criteria were based on previous publications in which the minimum criteria for the diagnosis of lymphoid malignancy was 60% or greater aberrant cells in a lymph node, or 5000 cells/μL or greater phenotypically homogeneous expansion of lymphocytes in peripheral blood . The control group consisted of T cells purified from lymph node and thymic tissue collected from 8 young, healthy, hound mix dogs that were being utilized for a surgical continuing education course.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Boxers and Golden retrievers (GRs) are highly represented amongst the group of dogs that develop an aggressive form of T cell lymphoma, histologically characterized as lymphoblastic lymphoma or peripheral T cell lymphoma not otherwise specified (PTCL‐NOS) . Another example includes a recent study in which small breed dogs were found to be over‐represented in the group of dogs that develops B cell chronic lymphocytic leukemia . Breed‐specific tendencies to develop particular disorders indicate a high likelihood for genetic risk factors underlying these diseases, and position the dog as a useful model for studying the role of genes in the development of lymphoproliferative disease.…”
Section: Introductionmentioning
confidence: 99%
“…The most common causes of paraproteinemia are myeloma‐related disorders, including multiple myeloma, cutaneous or noncutaneous extramedullary plasma cell tumors, immunoglobulin‐secreting B‐cell chronic lymphocytic leukemia, and Waldenstrom's macroglobulinemia . Veterinary literature reports that nonneoplastic processes, including infectious agents (canine heartworm, Ehrlichiosis and other rickettsial diseases, leptospirosis, and feline infectious peritonitis), inflammatory diseases or primary hyperparathyroidism, can produce a monoclonal type morphology on SPE; these may be more consistent with restricted polyclonal/oligoclonal gammopathies .…”
Section: Serum Protein Electrophoresis Diagnostic Categoriesmentioning
confidence: 99%